2021
DOI: 10.3390/insects12030221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oil Palm Pollinating Weevil (Elaeidobius kamerunicus) Population Density in Biparental dura × pisifera Hybrids on Deep Peat-Soil in Perak State, Malaysia

Abstract: This study was conducted to assess the Elaeidobius kamerunicus (EK) population density among the biparental dura × pisifera hybrids’ palms on deep peat-soil. Twenty-four hybrids derived from 10 genetic sources were used. Variance analysis showed that the EK population density varies between different oil palm hybrids, with a more noticeable variation of a low population mean in the male weevil across the hybrids. The highest weevil population mean/spikelet was attained on the third day of anthesis. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The F/B value is closely related to the fruit set of bunches. The fruit set value is influenced by several extrinsic factors, such as water [14], nutrition ,and pollination/pollinator [20,21]. Genetically, the F/B value has a low heritability value based on SNP and SSR marker tests compared to ODM and S/F values [22].…”
Section: Discussionmentioning
confidence: 99%
“…The F/B value is closely related to the fruit set of bunches. The fruit set value is influenced by several extrinsic factors, such as water [14], nutrition ,and pollination/pollinator [20,21]. Genetically, the F/B value has a low heritability value based on SNP and SSR marker tests compared to ODM and S/F values [22].…”
Section: Discussionmentioning
confidence: 99%
“…In yield improvement of oil palm in any selection and breeding program, fresh fruit bunch and oil yield are the primary motives. However, fruit set that enhances yield improvement of both fresh fruit bunch and oil yield is greatly influenced by parthenocarpic fruit (PCF), with a series of contributing factors such as planting materials, pollinating weevils, the ratio of sex inflorescence, as well as environmental factors [12,13]. In plant breeding, for rapid advancement to take place, a substantial amount of heritability and variation should provide adequate scope intended for a rejoinder to selection in the characters selected [28].…”
Section: Discussionmentioning
confidence: 99%
“…The progenies used in this present study were planted on a fibric peat soil by MPOB in September 2008 as trial 0.502 in Teluk-Intan research station, Bagan-Datuk. The peat soil was formed through fibric organic materials and it was equitably homogeneous and flat, exposed to a moderate distribution of rainfall [12,13]. The experimental environment had a relative humidity of about 85%, an average field temperature of 27 • C, with 32 • C maximum and 21 • C minimum, with around 2100 mm of total yearly rainfall [12].…”
Section: Research Location and Experimental Designmentioning
confidence: 99%
“…Predators, such as insectivorous rodents, birds, insects in the orders of Heteroptera, Hymenoptera, and Diptera, and spiders, can significantly influence the population dynamics of E. kamerunicus and affect their pollination behavior [ 13 , 52 , 76 , 77 ]. Omnivorous rodents, such as Rattus tiomanicus and Rattus tanezumi , feed on a variety of food sources, including E. kamerunicus , and can reduce weevil populations through predation.…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
“…For example, research has shown that black-throated Prinia in Indonesian oil palm ecosystems primarily feed on E. kamerunicus , which constitutes more than 75% of their diet. These birds specifically target male inflorescences during anthesis, making them vulnerable, as reported by [ 76 ]. However, the impact of these predators on E. kamerunicus populations and their pollination activity is not fully understood, and more research is needed to clarify their significance [ 27 ].…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%